2014
DOI: 10.1128/aac.00871-13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience of Colistin-Glycopeptide Combination in Critically Ill Patients Infected with Gram-Negative Bacteria

Abstract: A colistin-glycopeptide combination (CGC) has been shown in vitro to be synergistic against multidrug-resistant Gram-negative bacteria (MDR GNB), especially Acinetobacter baumannii, and to prevent further resistance. However, clinical data are lacking. We carried out a retrospective multicenter study of patients hospitalized in intensive care units (ICUs) who received colistin for GNB infection over a 1-year period, to assess the rates of nephrotoxicity and 30-day mortality after treatment onset among patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 24 publications
2
61
0
4
Order By: Relevance
“…This may improve the activity of a number of antibiotics which would otherwise have little effect (13). This approach is validated by reports of better clinical outcomes with unorthodox therapies for an increasing range of carbapenem-resistant bacteria (14)(15)(16). In this study, we assessed the activity of TGC in combination with COL against a range of CRE both in vitro and in vivo by using standard checkerboard and time-kill assays and a simple invertebrate model (Galleria mellonella) of infection and therapeutics (17-19) (we do acknowledge that currently the G. mellonella model lacks the required validation with regard to comparability with human therapy).…”
mentioning
confidence: 77%
“…This may improve the activity of a number of antibiotics which would otherwise have little effect (13). This approach is validated by reports of better clinical outcomes with unorthodox therapies for an increasing range of carbapenem-resistant bacteria (14)(15)(16). In this study, we assessed the activity of TGC in combination with COL against a range of CRE both in vitro and in vivo by using standard checkerboard and time-kill assays and a simple invertebrate model (Galleria mellonella) of infection and therapeutics (17-19) (we do acknowledge that currently the G. mellonella model lacks the required validation with regard to comparability with human therapy).…”
mentioning
confidence: 77%
“…Petrosillo N et al found no difference in 30-day mortality, in the 4 groups as follows: colistin alone, colistin-glycopeptide, colistin plus other anti-GNB drugs, colistin-glycopeptide plus other anti-GNB drugs (28). But it's also indicated in this study that the colistin-glycopeptide combination was a protective factor for mortality if administered for > 5 days.…”
Section: Colistin-glycopeptidementioning
confidence: 56%
“…No difference was found between IV colistin monotherapy or combination therapy with rifampicin (53), glycopeptides (28), fosfomycin (54), carbapenem or sulbactam (31,47). But the combination of intravenous colistin plus intravenous vancomycin is associated with an increased risk of renal failure (51).…”
Section: Nephrotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Otros antibióticos, como la colistina y la tigeciclina, se utilizan para el tratamiento contra microorganismos portadores de carbapenemasas (20,21), y nuestros aislamientos presentaron sensibilidad in vitro frente a estos dos agentes. Sin embargo, actualmente ya hay reportes de aislamientos portadores de KPC resistentes a estos antibióticos en Estados Unidos (22), Europa (23,24) Asia (25) y, más recientemente, en Suramérica (26).…”
Section: Resultsunclassified